Embracing Harmony: Exploring Tri Hita Karana-Based Corporate Social Responsibility Initiatives - Berliana, Ni Putu Cherline; Wiryanata, I Gusti Ngurah Agung; Rukmiyati, Ni Made Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine and understand the practice of Corporate Social Responsibility (CSR) based on Tri Hita Karana (THK) implemented by W Bali Seminyak. This study uses qualitative descriptive data analysis to extract data and information from data collection activities such as observation, interviews, and literature studies. The results prove that this hotel has upheld its obligations to God, fellow human beings, and the environment. This is shown by discussions about CSR activities in the hotel environment among informants who show the implementation of THK in routine hotel operations.